2021
DOI: 10.1111/acer.14654
|View full text |Cite
|
Sign up to set email alerts
|

Regionally specific gray matter volume is lower in alcohol use disorder: Implications for noninvasive brain stimulation treatment

Abstract: Background There is growing interest in neuromodulation‐based therapeutics as tools for individuals with alcohol use disorder (AUD). Through electromagnetic induction, techniques such as transcranial magnetic stimulation (TMS) can noninvasively depolarize cortical cells in the induced electrical field and monosynaptic afferents. The ability of TMS to modulate the brain is dependent upon two factors, which may be compromised in individuals with AUD: (1) gray matter volume (GMV) at the site of stimulation and (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 54 publications
(80 reference statements)
0
17
0
Order By: Relevance
“…Electrode montage (including electrode position, size, and orientation) can affect electric field distribution patterns, and our results [in line with previous dose-response findings ( Kim et al, 2014 ; Kasten et al, 2019 )] suggest that the electric field distribution patterns are a relevant factor for modulating brain activity and corresponding physiological and behavioral effects like craving. Other methodological aspects (e.g., number of participants, number of active sessions, and duration of each session), drug dependency profiles (e.g., type of substance, duration of abstinence, and state of dependency), and brain structural alterations in regions associated with SUDs [e.g., different cortical morphology ( McCalley and Hanlon, 2021 ; Soleimani et al, 2021b )] may also affect stimulation outcomes in the field of addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Electrode montage (including electrode position, size, and orientation) can affect electric field distribution patterns, and our results [in line with previous dose-response findings ( Kim et al, 2014 ; Kasten et al, 2019 )] suggest that the electric field distribution patterns are a relevant factor for modulating brain activity and corresponding physiological and behavioral effects like craving. Other methodological aspects (e.g., number of participants, number of active sessions, and duration of each session), drug dependency profiles (e.g., type of substance, duration of abstinence, and state of dependency), and brain structural alterations in regions associated with SUDs [e.g., different cortical morphology ( McCalley and Hanlon, 2021 ; Soleimani et al, 2021b )] may also affect stimulation outcomes in the field of addiction.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, previous studies showed that symmetric montages over DLPFC could diminish risk-taking behavior during a Balloon Analogue Risk Task (BART) [62,63], while asymmetric DLPFC stimulation shows no such effect [64]. Between montage difference in terms of peaks' strength only in the healthy group (not MUDs) suggest that generalization of the results obtained from EF distribution patterns fundamentally depends on the population of interest and highlights the importance of head modeling in tES protocol optimization in both individual and group levels [65,66].…”
Section: Bipolar Montages (Asymmetric Vs Symmetric) Induce Different ...mentioning
confidence: 96%
“…Furthermore, since we did not consider age/sex-matched clinical population and because the imaging protocols were different between the two groups, we did not directly compare our results between MUDs and healthy subjects as conducted by [47]. Because it has been reported that EF distribution patterns in brain stimulation studies may be different in the field of addiction compared to healthy subjects with respect to the brain anatomical alterations [65,66] and because sex differences in skull thickness, for example, would lead to differences in peak EF location/value, comparing EF peaks between SUDs and healthy subjects in age and sex-matched case-control cohorts could be further investigated in future studies. For instance, our results showed that the center of averaged EF peak location is deeper in the brain of our clinical population compared to healthy subjects.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…This is of particular relevance in AUD, wherein alcohol is known to induce widespread cortical atrophy ( 112 ). That said, a recent study investigating the distance from the scalp to the cortex at the dlPFC and mPFC among a sample of individuals with AUD and healthy controls did not find a significant difference between the groups ( 113 ).…”
Section: Research Gaps: Advancing Treatment For Audmentioning
confidence: 99%
“… Proposed theoretical electrical field models ( 113 ). (A) Targeting dACC stimulation and (B) targeting AIns stimulation.…”
Section: Research Gaps: Advancing Treatment For Audmentioning
confidence: 99%